2022
DOI: 10.7717/peerj.14303
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of circulating tumor DNA as a minimally invasive biomarker for hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Purpose This study aimed to assess the diagnostic performance of circulating tumor DNA (ctDNA) in hepatocellular carcinoma (HCC). Materials and Methods We enrolled all relevant studies published up to 5 January 2022. Three primary subgroups were investigated: qualitative or quantitative ctDNA analyses, combined alpha-fetoprotein (AFP), and ctDNA assay. In addition to the three primary subgroups, we also evaluated the diagnostic value of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Combining AFP with ctDNA assay resulted in an AUROC of 0.89, sensitivity of 0.82, and specificity of 0.84. The study demonstrated that ctDNA, especially mSEPT9, holds good diagnostic potential in HCC, but combining ctDNA with conventional serological assays like AFP can enhance diagnostic performance ( 73 ).…”
Section: Liquid Biopsy For Hcc Early Detectionmentioning
confidence: 99%
“…Combining AFP with ctDNA assay resulted in an AUROC of 0.89, sensitivity of 0.82, and specificity of 0.84. The study demonstrated that ctDNA, especially mSEPT9, holds good diagnostic potential in HCC, but combining ctDNA with conventional serological assays like AFP can enhance diagnostic performance ( 73 ).…”
Section: Liquid Biopsy For Hcc Early Detectionmentioning
confidence: 99%